2021
DOI: 10.3389/fgene.2021.641575
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of MicroRNAs in Hypertrophy and Ossification of Ligamentum Flavum: New Advances, Challenges, and Potential Directions

Abstract: Pathological changes in the ligamentum flavum (LF) can be defined as a process of chronic progressive aberrations in the nature and structure of ligamentous tissues characterized by increased thickness, reduced elasticity, local calcification, or aggravated ossification, which may cause severe myelopathy, radiculopathy, or both. Hypertrophy of ligamentum flavum (HLF) and ossification of ligamentum flavum (OLF) are clinically common entities. Though accumulated evidence has indicated both genetic and environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 111 publications
3
15
0
Order By: Relevance
“…Emerging evidence has demonstrated that dysregulated miRNAs is involved in the occurrence and progression of HLF [ 22 , 43 ]. Yu et al identified that miR-221 was down-regulated in HLF tissues, and overexpressing miR-221 inhibited the expression of collagens I and collagens III by sponging TIMP-2, thus inhibiting HLF formation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Emerging evidence has demonstrated that dysregulated miRNAs is involved in the occurrence and progression of HLF [ 22 , 43 ]. Yu et al identified that miR-221 was down-regulated in HLF tissues, and overexpressing miR-221 inhibited the expression of collagens I and collagens III by sponging TIMP-2, thus inhibiting HLF formation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no particularly effective conservative treatment to delay or reverse the HLF-induced LSCS except surgical decompression. Surgical removal of the hypertrophic ligamentum flavum can achieve spinal decompression, but not only the risks and postoperative complications of surgery are particularly prominent but also many patients with underlying diseases (such as diabetes, hypertension and hyperlipidemia) are intolerant to surgery [ 21 , 37 , 43 ]. Although fibrosis have been proved to be the key pathological feature of HLF, the precise mechanism of the pathology of LF fibrosis has not been fully elucidated [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the inclusion criteria ( 1 ): organism: Homo sapiens ( 2 ); expression profiling by microarray; and ( 3 ) samples: OLF ligament tissues and normal ligament tissues, an eligible high-throughput RNA-sequencing data (GSE106253) was downloaded from GEO for further analysis. The microarray data contains the mRNA information of ligamentum flavum tissue from 4 OLF patients and 4 healthy individuals.…”
Section: Methodsmentioning
confidence: 99%
“…Ossification of ligamentum flavum (OLF) is the major pathogeny of severe thoracic myelopathy characterized by abnormally heterotopic bone formation of the intraspinal ligament with unelucidated pathogenesis ( 1 ). To date, genetic, mechanical stress, degeneration, inflammatory, and metabolic factors have been found to be involved in the occurrence and progression of OLF ( 2 6 ).…”
Section: Introductionmentioning
confidence: 99%